2021
DOI: 10.1002/mus.27170
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and functional impacts of diaphragmatic involvement in patients with inclusion body myositis

Abstract: Background We evaluated the functional consequences of diaphragm involvement in patients with inclusion body myositis (IBM). Methods Ultrasound diaphragm thickening fraction (TFdi), lung function and dyspnea levels were compared between IBM patients and matched controls. Patients with IBM were grouped into “low” and “high” diaphragm activity based on TFdi values (with cutoff value being the lowest observed TFdi in the control group), and clinical characteristics were compared between groups. Results 20 IBM pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
1
3
0
4
Order By: Relevance
“…In case 3 we were able to demonstrate ultrasound evidence of diaphragmatic weakness. It is likely that severe respiratory failure in IBM to the extent of what was observed in this series is predominantly due to diaphragmatic weakness; selected reports have demonstrated concrete evidence of diaphragm involvement (26,31,32). Macroglossia was noted in two cases belonging to the second phenotype outlined in our series.…”
Section: Discussionsupporting
confidence: 49%
“…In case 3 we were able to demonstrate ultrasound evidence of diaphragmatic weakness. It is likely that severe respiratory failure in IBM to the extent of what was observed in this series is predominantly due to diaphragmatic weakness; selected reports have demonstrated concrete evidence of diaphragm involvement (26,31,32). Macroglossia was noted in two cases belonging to the second phenotype outlined in our series.…”
Section: Discussionsupporting
confidence: 49%
“…Ultrasound has also been used to assess diaphragm thickness in myositis and allows for the assessment of anatomy and function ( 126 ). Respiratory muscle involvement is reported in IIMs ( 127 ); in IBM, data are limited about prevalence and impact on functional capacity partly due to limited methods of assessing diaphragmatic involvement ( 128 ). Ultrasound has been shown to be effective in screening patients with IBM and has shown that diaphragm involvement in IBM is related to disease duration and has detrimental effects on exercise capacity and lung function ( 128 ).…”
Section: Ultrasoundmentioning
confidence: 99%
“…Respiratory muscle involvement is reported in IIMs ( 127 ); in IBM, data are limited about prevalence and impact on functional capacity partly due to limited methods of assessing diaphragmatic involvement ( 128 ). Ultrasound has been shown to be effective in screening patients with IBM and has shown that diaphragm involvement in IBM is related to disease duration and has detrimental effects on exercise capacity and lung function ( 128 ). More recently, studies have also shown utility in the use of ultrasound to assess diaphragm involvement in patients with immune checkpoint inhibitor-related myositis ( 129 ).…”
Section: Ultrasoundmentioning
confidence: 99%
“…Esta estratégia foi desenvolvida a partir de uma adaptação da ferramenta PICO Na Tabela 1 encontram-se informações dos estudos quanto aos tipos de estudos, número da amostra, média das idades e doença. Dos seis estudos selecionados, dois tratava-se de estudo caso-controle 11,12 , dois eram estudos controlados randomizados 13,14 , dois tratava-se de estudos transversais 15,16 . A espessura diafragmática (ED) foi descrita em adultos com as patologias: Doença Pulmonar Obstrutiva Crônica (DPOC) 11 ; Acidente Vascular Cerebral (AVC) 13 ; Câncer (CA) no pulmão 14 ; Charcot-Marie-Tooth 1A (CMT1A) 12 ; Anemia Falciforme (AF) 15 e Miosite por Corpos de Inclusão (MCI) 16 .…”
Section: Métodounclassified